US Special Forces and Counterinsurgency in Vietnam: Military Innovation and Institutional Failure, 1961-63, 1st edition - Ives, Christopher K. (Routledge, 2020)
This volume examines US Army Special Forces efforts to mobilize and train indigenous minorities in Vietnam.